Narrative inquiry - Wells, Kathleen (New York ; Oxford : Oxford University Press, 2011)
This pocket guide presents a reader-friendly introduction to narrative inquiry. It addresses major aspects of the design and implementation of a narrative research project, emphasizing established and emerging approaches to the analysis of narrative data.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Narrative inquiry (Research method); Social service